Adult attachment and drinking context as predictors of alcohol problems and relationship satisfaction in college students. (4th May 2018) - Hocking, Elise C.; Simons, Raluca M.; Simons, Jeffrey S.; Freeman, Harry
ABSTRACT: Background : Evidence suggests that for young adults, intimate partners influence each other's drinking patterns. Therefore, exploration of variables related to intimate partner relationships (such as attachment style) could broaden the current understanding of risk factors for alcohol problems in this demographic. Objectives : The current study examined the role of drinking context in the relationships among insecure attachment, alcohol problems, and relationship satisfaction. A path model was hypothesized where the relationship between insecure attachment and alcohol problems would be explained via two distinct drinking contexts (i.e., drinking with one's partner and drinking away from one's partner). It was also hypothesized that the relationship between insecure attachment and relationship satisfaction would be explained via these same two drinking contexts. Methods : Participants were 194 undergraduate students ages 18–25 who reported being in a monogamous intimate partner relationship for at least 90 days and had also consumed alcohol in the past 90 days. The sample was comprised of 76% women and 24% men. Results : The hypothesized direct relationship from anxious attachment to alcohol problems was significant; there were also significant direct paths from both anxious and avoidant attachment to relationship satisfaction. The hypotheses regarding indirect relationships were not supported. Conclusion : The results of this study contribute to the existing literature, in that they suggest that drinking in the context of an intimate relationship may not directly affect relationship satisfaction in this population. However, relationship functioning still appears to be an important variable to consider in the prevention and treatment of alcohol-related problems affecting college students.